1990
DOI: 10.1111/j.1365-2494.1990.tb01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of prairie grass (Bromus willdenowii Kunth) affected by sowing date and the head smut fungus (Ustilago bullata Berk.)

Abstract: Effects of sowing date, fungicide seed treatments, and the head smut fungus Ustilago bullata Berk, on establishment, herbage, and seed production of prairie grass cv. Grasslands Malua {Bromus willdenowii Kunth) were measured in autumn-and spring-sown field trials in New Zealand.Autumn seedling establishment from thiramtreated seed relative to untreated seed was increased by 27% from the earliest sowing (early March), and by 65% from the latest sowing 8 weeks later. Infestation of seed with ustilospores of U. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Endophyte-infected subplots produced more biomass than E-ones inoculated with the smut, and smut inoculated E-subplots produced less biomass than the S-controls. Negative effects of U. bullata on biomass production were also observedin field studies with B. catharticus (Falloon 1976(Falloon , 1979Falloon and Hume 1988;Falloon and Rolston 1990). In our experiment, the higher amount of biomass produced during the first year by plants in E+ or E-S-treatments was due to the higher soil cover and not to the size of the plants, since the ratio between biomass production and soil cover in E+ subplots was not significantly higher than in the E-subplots (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Endophyte-infected subplots produced more biomass than E-ones inoculated with the smut, and smut inoculated E-subplots produced less biomass than the S-controls. Negative effects of U. bullata on biomass production were also observedin field studies with B. catharticus (Falloon 1976(Falloon , 1979Falloon and Hume 1988;Falloon and Rolston 1990). In our experiment, the higher amount of biomass produced during the first year by plants in E+ or E-S-treatments was due to the higher soil cover and not to the size of the plants, since the ratio between biomass production and soil cover in E+ subplots was not significantly higher than in the E-subplots (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…catharticus in New Zealand. In this species, under field conditions, the inoculation with U. bullata significantly reduced seedling establishment (Falloon and Rolston 1990), biomass production (Falloon 1976(Falloon , 1979Falloon and Hume 1988;Falloon and Rolston 1990) and infected plants presented poorer persistence (Falloon and Hume 1988) than non-infected plants. In greenhouse experiments, the pathogen reduced seedling emergence rate and survival (Falloon 1976), reduced the overall size of infected plants and caused their complete sterility (García-Guzmán et al 1996).…”
Section: Introductionmentioning
confidence: 84%
“…Uninfected plants compensated for the low productivity and death of infected plants by producing more tillers. In subsequent studies, Falloon and Rolston (1990) found that autumn establishment of Matua was improved when Matua seeds were treated with a fungicide, whereas spring establishment of Matua was not improved; however, the beneficial effects of fall seed treatment lasted only 18 wk.…”
Section: The Effects Of Head Smut (Caused By Ustilago Bullatamentioning
confidence: 99%
“…When reproductive structures are affected, the infected grass host can display both fungal fruiting bodies and seed‐bearing inflorescences or entirely aborted inflorescences in which all flowers are replaced by fungal fruiting bodies, that is, sori bearing teliospores (Piepenbring et al, 1998; Xia et al, 2020). Therefore, smut fungi have the potential to substantially influence the seed output and successful reproduction of grasses (Falloon and Rolston, 1990). Moreover, because the relationship between pathogenic fungi and their hosts can be influenced by environmental conditions (e.g., Finch, 2010; Meena et al, 2011; Simler‐Williamson et al, 2021), human environmental management activities can affect pathogen infection and colonization.…”
mentioning
confidence: 99%